136k views
4 votes
Which expression is equivalent to (picture attached)

Which expression is equivalent to (picture attached)-example-1
User Oddman
by
5.1k points

2 Answers

6 votes

Answer:

Its the last one a^2/b.

Explanation:

(a^6 b^-3)^1/3

= a ^(6 * 1/3) b^(-3*1/3)

= a^2b^-1

= a^2/b.

User Naseem
by
5.5k points
6 votes

Answer:

Explanation:

(a⁶b⁻³)∧1/3

(a^6*1/3) (b^-3*1/3)

a²b⁻¹

a²*1/b

a²/b

User Petru
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.